A concurrent ultra‐fractionated radiation therapy and temozolomide treatment: A promising therapy for newly diagnosed, inoperable glioblastoma. Issue 6 (20th November 2015) - Beauchesne, P.; Quillien, V.; Faure, G.; Bernier, V.; Noel, G.; Quetin, P.; Gorlia, T.; Carnin, C.; Pedeux, R.
Abstract : We report on a phase II clinical trial to determine the effect of a concurrent ultra‐fractionated radiotherapy and temozolomide treatment in inoperable glioblastoma patients. A phase II study opened; patients over 18 years of age who were able to give informed consent and had histologically proven, newly diagnosed inoperable diagnosed and supratentorial glioblastoma were eligible. Three doses of 0.75 Gy spaced apart by at least 4 hr were delivered daily, 5 days a week for six consecutive weeks for a total of 67.5 Gy. Chemotherapy was administered during the same period, which consisted of temozolomide given at a dose of 75 mg/m 2 for 7 days a week. After a 4‐week break, chemotherapy was resumed for up to six cycles of adjuvant temozolomide treatment, given every 28 days, according to the standard 5‐day regimen. Tolerance and toxicity were the primary endpoints; survival and progression‐free survival were the secondary endpoints. In total, 40 patients were enrolled in this study, 29 men and 11 women. The median age was 58 years, and the median Karnofsky performance status was 80. The concomitant ultra‐fractionated radiotherapy and temozolomide treatment was well tolerated. Complete responses were seen in four patients, and partial responses were reported in seven patients. The median survival from the initial diagnosis was 16 months. Several long‐term survivors were noted. Concurrent ultra‐fractionated radiation therapy and temozolomide treatment are well accepted by the patients. The results showed encouraging survival rates for these unfavorable patients. Abstract : What's new? Glioblastoma (GBM) is considered to be one of the most radio‐resistant types of tumor. Standard treatment includes brain radiotherapy (RT) plus chemotherapy with temozolomide (TMZ). New treatment strategies are urgently needed, however. In this phase II clinical trial, the authors treated inoperable GBM patients with TMZ chemotherapy plus "ultra‐fractionated" brain irradiation (low‐dose irradiation given several times a day, over six weeks). The results were encouraging in terms of improved survival rates, and the treatment combination was well tolerated. This unique approach thus shows significant promise as a new treatment modality for GBM.